Comparison of microcurrent and low level laser therapy on matrix metalloproteinases and tissue inhibitors of metalloproteinases expressions in surgical wound healing - Ayman Mohammed El Makakey; Mohammed H. Hassan; Nehad A. Abo-zaid; Bakheet E. M. Elsadek; Mahmoud A. Hifny; Radwa Mahmoud Elsharaby; Mohammed E. Ali (Scientific Reports)
Abstract Purpose The purpose of this study was to compare the modulation effects of Microcurrent Therapy (MT) and Low-Level Laser Therapy (LLLT) on Matrix Metalloproteinases (MMPs) and tissue inhibitors of Metalloproteinases (TIMPs) expressions during healing of surgical wounds using appendectomy wound as a model. Methods Ninety patients who recently underwent appendectomy were randomly divided into 3 main groups of equal numbers. All cases in the three groups received ordinary medical therapy. Moreover, group A (MT group) received Microcurrent Therapy for 20 min. In addition to a designed physical therapy treatment protocol for 20 min. Group B (LLLT group) received Low-Level Laser Therapy for 20 min., plus the same designed physical therapy treatment protocol for 20 min. Group C (placebo group) received placebo shame LLLT for 20 min. plus the same designed physical therapy treatment protocol for 20 min. Enzyme-linked immunosorbent assay (ELISA) and Western Blot Technique (WBT) were used to determine expression levels of MMP-8, MMP-9, and TIMP-1 at the beginning of treatment and after the end of twelve successive sessions. Results Following therapies, results showed a statistically significant decrease in the MMP-8 and MMP-9 expressions with significantly increased expression levels of TIMP-1 in each group separately (P < 0.05). These changes in the expression levels towards proper healing of surgical wounds were more obvious in MT and LLLT groups compared to the placebo group, with significantly better effect in the LLLT group compared to the MT group . Conclusion Microcurrent therapy and low-level laser therapy have a notable impact in improving wound healing process as they can significantly affect the expression levels of matrix metalloproteinases and tissue inhibitors of metalloproteinases towards good prognosis of healing process and decreasing possible wound healing complication, with superior effect of low-level laser therapy.